Association of Chronic Kidney Disease Stage and Pulmonary Edema through Radiological Imaging - Shahzad Shokat, Fazl-E-Mateen, Sarfraz Ahmed, Alishba Tariq, Sundus Sehar, Muhammad Salman Rehman (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Chronic kidney disease is a progressive condition that can lead to end-stage renal disease, significantly impacting cardiovascular and pulmonary health. Radiological imaging, particularly chest x-ray plays a crucial role in detecting and evaluating pulmonary edema in chronic kidney disease patients at different stages. Objective: To find the association of chronic kidney disease stage and pulmonary edema through radiological imaging. Study Design: Cross-sectional study. Place and Duration of Study: Departments of Nephrology & Radiology, Khawaja Muhammad Safdar Medical College Sialkot from 1st March 2023 to 31st August 2023. Methodology: Sixty patients who were clinically diagnosed with chronic kidney disease and age between 12-70 years were enrolled. Each patient had demographic details as well as clinical symptoms, and clinical history was documented. Each patient then further underwent radiological examination which comprised of chest X-rays. Additional patient characteristics observed included age, gender, and underlying conditions such as hypertension, diabetes mellitus, and obstruction and reflux uropathy. Laboratory parameters such as hemoglobin, urea, creatinine, and estimated glomerular filtration rate were also analyzed for assessing the staging of kidney disease and finding its association with the pulmonary edema if presented. Results: In terms of pulmonary edema, all patients in Stage 1 and Stage 2 (100%) showed no edema, while in Stage 3, 33% had mild edema. In Stage 4, 67% had moderate edema, and in Stage 5, all patients (100%) had severe edema. Symptom prevalence also increased with disease progression: in Stage 5, 100% of patients had shortness of breath and fatigue, 100% had a cough, and 80% had orthopnea. Treatment strategies varied across stages, with 33% of Stage 3 patients requiring diuretics, 67% in Stage 4 requiring diuretics, and 100% of Stage 5 patients needing diuretics, dialysis, oxygen therapy, and fluid restriction. Conclusion: It is concluded that the severity of pulmonary edema increases with the progression of chronic kidney disease (CKD), with no edema observed in the early stages (Stage 1 and Stage 2), mild edema in Stage 3, moderate edema in Stage 4, and severe edema in Stage 5. The prevalence of symptoms such as shortness of breath, fatigue, and cough also rises as the disease advances. Keywords: Chronic kidney disease (CKD), Pulmonary edema, Association, End stage renal disease (ESRD), Estimated glomerular filtration rate (eGFR)